Molecular and serological evaluation of visceral leishmaniasis in domestic dogs and cats in Maragheh County, north‐west of Iran, 2018–2021. Issue 5 (27th May 2022) - Soleimani, Ali; Mohebali, Mehdi; Gholizadeh, Saber; Bozorgomid, Arezoo; Shafiei, Reza; Raeghi, Saber
Abstract: Objective: Zoonotic visceral leishmaniasis (VL) is caused by Leishmania infantum, of which dogs are the main reservoir. VL is endemic in the Middle East, also in some parts of Iran. Following reports of new cases of VL in children in Maragheh County, the non‐endemic area of the disease, we encouraged to conduct a preliminary study on domestic dogs and cats to identify their potential role as reservoirs for the disease. Materials and Methods: This study was conducted during a period of 3 years from 2018 to 2021. Two hundred ownership dogs and 25 cats from Maragheh County, north‐west of Iran, were randomly screened. Blood samples were collected. A direct agglutination test (DAT) was used for the detection of anti‐ L. infantum antibodies. Furthermore, buffy coat samples from the L. infantum seropositive animals were examined to detect parasite presence using polymerase chain reaction. Results: Out of the total of 200 ownership dogs evaluated, 170 (85%) were male and 30 (15%) were female with a mean age of 4.3 years. Anti‐ L. infantum antibodies (IgG cut‐off ≥ 1:320) were observed in 3.5% of dogs (7/200) by the DAT test. All seropositive dogs were identified in the first year of examination. Regarding molecular approaches in seropositive dogs, two samples were positive for a 565 bp kDNA minicircle gene specific for L. infantum . During the study period, no seropositive case was detected in the cats examined. Conclusions: This study shows that the domestic cycle of L. infantum has been established in the studied region. It is necessary to increase the awareness and monitoring of the disease with the study of wild reservoirs periodically.